The electricity of every living thing eaudiobook A woman's walk in the wild to find her way home. - May, Katherine (Melville House, 2021)
The New York Times bestselling author of Wintering writes a life-affirming exploration of wild landscapes, what it means to be different and, above all, how we can all learn to make peace with our own unquiet minds . . . In anticipation of her 38th birthday, Katherine May set out to walk the 630-mile South West Coast Path. She wanted time alone, in nature, to understand why she had stopped coping with everyday life; why motherhood had been so overwhelming and isolating; and why the world felt full of expectations she couldn't meet. She was also reeling from a chance encounter with a voice on the radio that sparked her realisation that she might be autistic. And so begins a trek along the ruggedly beautiful but difficult path by the sea that takes readers through the alternatingly frustrating, funny, and enlightening experience of re-awakening to the world around us... The Electricity of Every Living Thing sees Katherine come to terms with that diagnosis leading her to re-evaluate her life so far — with a much kinder, more forgiving eye. We bear witness to a new understanding that finally allows her to be different rather than simply awkward, arrogant or unfeeling. The physical and psychological journeys of this joyous and inspiring book become inextricably entwined, and as Katherine finds her way across the untameable coast, we learn alongside her how to find our way back to our own true selves.